Public Transport Mode Model Selection for public Transport Users in the City of Makassar Based on the Change of Speed Travel Variables - Syahlendra, Syahlendra (INTEK: Jurnal Penelitian, 2020)
The increasing number of private vehicles shows that the public transportation system in Makassar has not been maximized. this is also due to the absence of other alternative public transportation modes that can be used by the community in their activities. This study aims to determine the preference of public modes of choice if offered other alternatives, especially public transport with greater capacity. Public transportation offered in this study is busway and monorail. In this study the community was faced with 3 modes of choice namely city transportation, monorail, and busway. The data collection method used was a survey with stated preference based questionnaires, which reviewed nine conditions for variable change in travel speed. The construction of the model was carried out using STATA software and city transportation was used as the base outcome. The model is based on discrete selection models and is analyzed by the multinomial logit model. The results showed that in the nine conditions of change in travel speed, the mode of city transportation was still more dominantly chosen by the community.